Carbon nanohorns as integrative materials for efficient dye-sensitized solar cells - Costa, Rubén D (Advanced materials (Deerfield Beach, Fla.), 2013)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.